HISTORY AND FUTURE OF LANDSCAPING HORTICULTURE (American Journal of Interdisciplinary Research and Development, 2022)
Beauty and purity are one of the simplest human qualities, which a person always strives for. From ancient times the people have been trying to make their habitats beautiful and prosperous. The article discusses the history of scenic gardening and floriculture, the prospects for its development.